Role of observational studies in supporting extrapolation of efficacy data from adults to children with epilepsy — A systematic review of the literature using lacosamide as an example. (July 2019) - Arzimanoglou, A.; Kalilani, L.; Anamoo, M.A.; Cooney, M.; Golembesky, A.; Taeter, C.; Bozorg, A.; Tofighy, A.; Wheless, J.
Abstract: Extrapolation of efficacy data from adults to children is accepted for focal epilepsy – the antiepileptic drug, lacosamide, has been approved for the treatment of children ≥4 years of age on this basis. Since many small-scale, open-label studies are reported in the literature before approval, a systematic review was conducted to ascertain whether results of these could be used to support extrapolation in epilepsy in the future. In the absence of randomised trials, a second analysis was conducted for reports on lacosamide use in adults with generalized epilepsies. Twenty-seven articles were included in the paediatric qualitative synthesis, and 14 in the adult. Paediatric studies were analysed separately based on seizure type: focal, generalised and mixed. In focal epilepsy, safety and seizure-related findings mirrored those observed in the adult Phase II/III trials, supporting the feasibility of data extrapolation. Few studies reported outcomes in children with epilepsies associated with generalised seizures, and those that included children with different seizure types, mostly did not provide results separately. Lacosamide treatment appeared beneficial for children and adults experiencing tonic-clonic and myoclonic seizures. Reports of seizure aggravation were inconsistent and, in many cases, could not be clearly attributed to lacosamide. Given the absence of sufficient data, evidence for the feasibility of extrapolation was not as clear-cut as it was in focal epilepsy. These results highlight the complexities of conducting trials in the generalised epilepsy setting, and the importance of studies in the real-life setting and of analysing efficacy data per generalized seizure type and syndrome. Highlights: Extrapolation of efficacy data from adults to children is accepted in focal epilepsies. LCM data from open-label paediatric studies supported focal epilepsy extrapolation. In generalised epilepsies, evidence for extrapolation feasibility was not clear-cut. Efficacy results should be analysed per generalized seizure type and per syndrome. Overall, LCM's safety profile in children with various epilepsies was favourable.